Special Issue: Evolutionary perspectives on salmonid conservation and management - Waples, Robin S (Blackwell Publishing Ltd, 2008)
This special issue of Evolutionary Applications comprises 15 papers that illustrate how evolutionary principles can inform the conservation and management of salmonid fishes. Several papers address the past evolutionary history of salmonids to gain insights into their likely plastic and genetic responses to future environmental change. The remaining papers consider potential evolutionary responses to climate warming, biological invasions, artificial propagation, habitat alteration, and harvesting. All of these papers consider how such influences might alter selective regimes, which should then favour plastic or genetic responses. Some of the papers then go on to document such responses, at least some of which are genetically based and adaptive. Despite the different approaches and target species, all of the papers argue for the importance of evolutionary considerations in the conservation and management of salmonids.